Economics, quality, nutrient uptake and water productivity of fennel (Foeniculum vulgare) as influenced by micro-irrigation under different planting patterns - Jat, M.L.; Shivran, A.C.; Dhaka, M.S.; Jeetarwal, R.L.; Naga, Sunder Devi (Annals of Agricultural Research, 2016)
Economics, quality, nutrient uptake and water productivity of fennel (Foeniculum vulgare) as influenced by micro-irrigation under different planting patterns M.L. Jat*, A.C. Shivran, M.S. Dhaka, R.L. Jeetarwal and Sunder Devi Naga Department of Agronomy, S.K.N. College of Agriculture, Jobner, Jaipur, Rajasthan-303 329